Análise comparativa entre o controlador PID-Fuzzy e o PID convencional aplicados à estabilização da atitude de um quadrimotor - Oliveira, Sameque Farias Cunha de (Brasil, 2015)
The quadrotor is a type of aerial vehicle that has a complexity related to control, much less than other UAV as a traditional helicopter. However, as propellers and engines, for example, are not exactly the same even if the engine speed are receiving the same references, the thrust produced by the propeller, rotor system is di_erent. Thus, the system is naturally unstable. Furthermore, it can be said that the quadrotor is a underactuated system, since there are four input variables (speed of four engines) and six output (x, y, z, roll, pitch, yaw) of the couplings without speaking and the variables relating aerodynamic non-linearities, drives, etc. Design a single controller that can handle these circumstances is an extremely complicated task. This work presents a comparison between the PIDFuzzy and PID controls, which are used to stabilize the four-engine attitude in a shorter time. In addition to the results of the simulations for both control techniques in which it was found that both controllers are able to stabilize the model PID-Fuzzy better results than conventional PID
Keywords: Quadrimotor; Estabilização; PID; Fuzzy; Quadrotor; Stabilization; PID; Fuzzy; ENGENHARIAS::ENGENHARIA ELETRICA